Customer satisfaction level of prepaid subscribers of Airtel Bangladesh Limited - Rahman, Abdur (BRAC Business School (BBS), BRAC University, 2012)
An Internship Report Presented to the Faculty of Business Administration in Partial Fulfillment of the Requirements for the Degree of Bachelor of Business Administration, BRAC University.